Does Public Disagreementon Monetary Policy Unsettle the Markets? - Samiei, Hossein (IMF Working Papers; Working Paper, 1997)
Publication of minutes of monthly monetary policy meetings between the Chancellor of the Exchequer and the Governor of the Bank of England was a conspicuous feature of the United Kingdom's inflation targeting framework from 1994 through April 1997. It was intended to reinforce credibility by publicizing the criteria on which policy was decided. On some occasions, however, these minutes revealed disagreement between the participants. This paper examines whether such disagreement unsettled the markets and detracted from credibility.